Navigating the Cyber Threat Landscape: A Comprehensive Analysis of Attacks and Security in the Digital Age - Jony, Akinul Islam; Hamim, Sultanul Arifeen (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2023)
In this contemporary digital age, cybersecurity stands as a crucial linchpin amid the expanding role of technology in our lives, encountering numerous challenges. This review addresses the imperative need for robust cybersecurity measures as malicious actors continually innovate methods to exploit vulnerabilities in computer systems, networks, and data. The exploration delves into the multifaceted realm of cybersecurity attacks, unveiling the evolving threat landscape and their profound implications. From cybercriminals utilizing phishing attacks to the covert tactics of malware and the disruptive potential of Denial of Service (DoS) and Distributed Denial of Service (DDoS) attacks, including Phishing, Zero-Day Exploits, Man-in-the-Middle, and SQL Injection Attacks, the cybersecurity battleground is ever-expanding. The study systematically categorizes cyber threats, scrutinizes their distinctive characteristics, and elucidates the modus operandi of each attack type. Through a meticulous dissection of cybercriminal methods and motivations and a comprehensive evaluation of countermeasure efficacy, this review offers indispensable insights for securing our digital future in an era marked by escalating interconnectivity and technological dependence.